Method for configuration synthesis of metamorphic mechanisms based on functional analyses. (May 2018) - Tian, Hai-bo; Ma, Hong-wei; Ma, Kun
Highlights: The role of the source mechanism in metamorphic mechanism synthesis is indicated. The configuration transformation modes of metamorphic mechanism are summarized. A method for configuration synthesis of metamorphic mechanisms is proposed. Abstract: Metamorphic mechanisms could change their configuration continually to accommodate different task requirements. From the perspective of the entire working cycle, the metamorphic mechanism is responsible for the synthesis of all working-phase mechanisms. The source-metamorphic mechanism, which is obtained by the aggregation of a series of working-phase mechanisms, is focal to the configuration synthesis of these mechanisms and to metamorphic joint design. The metamorphic modes can be classified into five types, including the geometry, motion, force, driving joint, and combined metamorphic mode. Based on the above, a method for configuration synthesis of metamorphic mechanisms is introduced herein. Firstly, the number and types of the degrees-of-freedom (DOFs) of the source-metamorphic mechanisms can be acquired based on an aggregated operation applied on the DOFs of the working-phase mechanisms. The possible configurations of the source-metamorphic mechanism can be obtained using traditional synthetic methods. The metamorphic joints and source-metamorphic mechanisms are then obtained by selecting and integration operations. Finally, the entire working process of the metamorphic mechanism is described using metamorphic equations. The mechanism of a loading manipulator for a garbage truck was developed to demonstrate the proposed method. The results showed that the proposed method is practical and simple.